Preparation, in Vitro Gastrointestinal Digestion and Antioxidant Activity of Ginkgo biloba Peptides-Zinc Chelate - Yi ZHENG; Shiying LI; Chuang LI; Xiaorui ZHOU; Yanan CHEN; Xiuyun ZHANG; Yinyu ZHANG (Shipin gongye ke-ji, 2023)
The aim of this study was to optimize the preparation process of Ginkgo biloba peptides-zinc chelate (Zn-GBP), and analyze its in vitro gastrointestinal digestion and antioxidant activity. The preparation process of Zn-GBP was optimized by single factor test and response surface method. The bioavailability of zinc ions in the Zn-GBP was determined by in vitro simulated gastrointestinal digestion. Furthermore, the in vitro antioxidant activity of Zn-GBP was evaluated using DPPH free radical scavenging ability, ABTS+ free radical scavenging ability and reducing ability. The results showed that the optimum preparation parameters were as follows: mass ratio of Ginkgo biloba peptides to zinc 3:1, chelating pH 8.2, chelating temperature 70 ℃, and chelating time 2 h. Under these parameters, the chelation rate was 49.23%±0.35%, and the chelate yield was 42.34%±0.45%. The solubility and permeability of zinc ions in Zn-GBP were significantly higher than those in inorganic zinc salts (P<0.05), indicating that Zn-GBP had better bioavailability. Zn-GBP showed strong scavenging activities against DPPH free radical and ABTS+ free radical, with EC50 values of 101.0 and 83.6 mg/L, respectively, and it also has strong reducing ability. Moreover, the in vitro antioxidant activity of Zn-GBP was higher than that of Ginkgo biloba peptides.